Impact of Non-Surgical Periodontal Treatment of Generalized Chronic Periodontitis on Quality of Life - Sema Merve Altıngöz; Canan Önder; Sivge Kurgan; Meral Günhan; Hassan Behravan; Cem Gurgan (Ankara University, 2022)
Aim: In recent years, after treatments variety of measurement scales are used to record the extent and impact of the treatment on quality of patient's life. Among these scales, Oral Health Impact Profile (OHIP-49) and a shorter version of that OHIP-14 are the most comprehensive, accessible and common ones. Our aim was to evaluate the effect of non-surgical periodontal therapy on quality of generalized chronic periodontitis patients' life by using the Turkish version of the OHIP-14 scale (OHIP-14-TR). Method: 58 patients (37 men and 21 women) diagnosed with generalized chronic periodontitis and requiring non-surgical periodontal therapy were recruited in this study. All patients were asked to fill in a form containing demographic, socio-economic information, reason of dental visit and oral hygiene habits. Clinical periodontal parameters (Plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment loss (CAL), and bleeding on probing (BOP)) were recorded at baseline, and one month after treatment. Non-surgical periodontal treatment containing scaling and root planning was performed during one week in two seperate sessions. OHIP-14-TR questionnaires have been filled out before and after treatment. Results: There were significant decreases in all periodontal parameters and OHIP-14-TR one month after non-surgical periodontal treatment (p0.05). Significant positive correlation was found between physical pain, and BOP and PPD. After periodontal treatment, BOP, PPD, and physical pain decreased. Conclusion: According the results of this study, it was revealed that non-surgical periodontal treatment was effective in improving the quality of life of patients.